Blind SNR estimation for OFDM signals in cognitive radio - Ming-qian LIU; Bing-bing LI; Ning-jie TANG; Zhao LI (Tongxin xuebao)
The traditional blind SNR estimation algorithms had problems of poor performance and high computation complexity for OFDM systems in cognitive radio with low signal to noise ratio(SNR)and multi-path channel conditions,in view of which a novel blind SNR estimation method for orthogonal frequency division multiplexing(OFDM)signals was proposed.Firstly,the channel order was roughly estimated by utilizing the characteristics of autocorrelation function to determine the data interval which was free of inter-symbol interference(ISI).Secondly,the signal average power was estimated by computing the autocorrelation values of data in the determined interval.Finally,the noise average power was estimated by utilizing the characteristics that the data in cyclic prefix which was replication of part useful data.So the SNR of the received signals could be estimated.The simulation results show that the proposed method doesn’t need any prior information and has better performance and lower computation complexity,which is more suitable for OFDM systems in cognitive radio.